Literation Abilities of Elementary School Students in Kupang District, NTT Based on Five Basic Reading Skills NTT - Marselus Robot; Karus Maria Margareta; Andreas Ande; Darius Mauritsius (Budapest International Research and Critics University, 2022)
This study aims to determine the literacy level of elementary school children from grade 1 to grade 3 in Kupang Regency, East Nusa Tenggara (NTT) based on four basic literacy skills, namely: (1) letter knowledge; (2) vocabulary or vocabulary; (3) reading fluency; (4) reading comprehension. The status of this research is a collaboration between the Nusa Cendana University Research Institute and the Sayangi Tunas Cilik Foundation (YSTC) Kupang. The study was conducted at 56 elementary schools spread over 7 sub-districts in Kupang Regency, NTT. The study population was 5085 children. Sampling of children in this study used the Slovin formula with an error rate of 2%. Samples were taken of as many as 1678 children. Data on children's literacy skills were taken using standardized tools from YSTC. These tools are already available in the form of a digital questionnaire. Data collection using a tablet with a face-to-face interview method (1 child with 1 enumerator). As many as 60% of children in the lower grades (grades I, II, III) of Elementary Schools in Kupang Regency are able to read. The specific findings of this study: (1) girls have higher literacy skills in the five basic literacy skills. (2) the role of the mother is more dominant in helping children read at home. (3) the higher the level (grade) the smaller the difference in literacy skills between boys and girls.